Yakut Northern Complex Expedition of 1964-1965 - A. A. Suleymanov (Научный диалог, 2019)
The article presents a pioneering in historiography attempt of scientific understanding of the history of the Yakut Northern Complex Expedition during 1964-1965, organized by the Yakut branch of the Siberian branch of the Academy of Sciences of the USSR with the support of the leadership of Yakutia. Due to the low degree of introduction of the expedition results into scientific circulation the research is based mainly on the analysis of the complex identified by the author of archival material. The work carried out made it possible to establish the personal composition of the expedition, the methodology of research, their geography and main directions. At the same time, the analysis of the key provisions developed by the participants of the expedition was carried out. The archival material introduced into scientific circulation may be of interest as a source of objective information on the socio-economic situation of the population of the Arctic regions of Yakutia in the 1960s. It is noted that the Yakut Northern Complex Expedition to date remains the only academic initiative implemented on such a scale, in which, on the basis of studies of a wide range of scientific problems and the coverage of a large part of the Arctic regions of the Republic, an integrated approach to ensuring the socio-economic development of these largely unique territories was laid. In addition, it is shown that this research initiative was one of the important attempts initiated in the region to revise the parameters of the resource model for the development of the Northern spaces that prevailed in the Soviet Union.